Improved The Learning Achievement of Elementary School Students Through The - Winingsih, Rahayu (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2021)
The purpose of this study is to find out the improvement of elementary school students' learning achievement through the medium of picture word cards. The problem in this study is still the low learning achievement of students seen from the initial test of learning achievement. This research took place in class I SDN Babatan IV/459 Surabaya. The school is located at Jalan Raya Menganti Babatan Wiyung District of Surabaya City. The research time was carried out in semester 1 (odd) in October of the 2020/2021 School Year. The subject of this study was a student of class I SDN Babatan IV /459 Surabaya which amounted to 28 students. This research design is class action research (PTK) through stage flow (planning, research action, data collection and data analysis) carried out with two cycles. The result of this study is an increase in student learning achievement in each lesson cycle with a minimum completion criteria (KKM) of 70, cycle I completed learning of 15 students or 60% of students who have achieved the minimum completion criteria with an average score of 72.95. While cycle II has increased, 28 students completed their studies or 100% of students have achieved the minimum completion criteria with an average score of 85.4.